Solusi Peningkatan Kesejahteraan Guru PAUD dalam Rangka Meningkatkan Kualitas Layanan Pendidikan di Sumatera Barat - Putri Nabila Agustin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Early Childhood Education (PAUD) honorary teachers in West Sumatra face serious welfare challenges, with incomes far below the Provincial Minimum Wage (UMP). This condition affects work motivation, limits access to professional development, and reduces the quality of early childhood education services. This study aims to analyze the current welfare conditions of PAUD honorary teachers, identify the factors contributing to low welfare, and offer strategic solutions involving the government, PAUD institutions, the community, and the teachers themselves. This research employed a literature review method by examining scientific journals, educational department reports, statistical data, government regulations, and supporting theories such as Human Capital and Work Motivation. The findings indicate that low welfare is caused by limited regional government budgets, reliance on parental fees, weak legal status of PAUD teachers, limited certification opportunities, and insufficient CSR and community support. Recommended solutions include increasing government funding, expanding ASN/PPPK recruitment opportunities, strengthening institutional management, collaborating with private sectors, and enhancing teacher competence through continuous training. In conclusion, improving the welfare of PAUD teachers is an urgent step to strengthen the quality of early childhood education services and support the achievement of national education goals from an early age.